Advanced Method for Calculations of Core Burn-Up, Activation of Structural Materials, and Spallation Products Accumulation in Accelerator-Driven Systems - A. Stankovskiy; G. Van den Eynde (Science and Technology of Nuclear Installations)
The ALEPH2 Monte Carlo depletion code has two principal features that make it a flexible and powerful tool for reactor analysis. First of all, it uses a nuclear data library covering neutron- and proton-induced reactions, neutron and proton fission product yields, spontaneous fission product yields, radioactive decay data, and total recoverable energies per fission. Secondly, it uses a state-of-the-art numerical solver for the first-order ordinary differential equations describing the isotope balances, namely, a Radau IIA implicit Runge-Kutta method. The versatility of the code allows using it for time behavior simulation of various systems ranging from single pin model to full-scale reactor model, including such specific facilities as accelerator-driven systems. The core burn-up, activation of the structural materials, irradiation of samples, and, in addition, accumulation of spallation products in accelerator-driven systems can be calculated in a single ALEPH2 run. The code is extensively used for the neutronics design of the MYRRHA research facility which will operate in both critical and subcritical modes.